Literature Review: The Role of Natural Science Education in Developing Students' Higher-Order Thinking Skills - Eldza Rosmiatin Nafiz; Siska Afrilianti; Asyil Arifah (Indonesian Journal of Applied Science and Technology, 2026)
Higher-Order Thinking Skills (HOTS) are essential 21st-century competencies, particularly in science education which emphasizes critical, analytical, and problem-solving thinking. This study systematically analyzes science education’s role in developing students' HOTS using a Systematic Literature Review (SLR) methodology. Fifteen indexed scientific articles published between 2019 and 2025 were selected from Google Scholar and national journals through structured identification, screening, eligibility, and inclusion processes. Findings reveal that student-centered models such as Problem-Based Learning (PBL), Inquiry Learning, and Project-Based Learning effectively enhance HOTS. Additionally, digital media, interactive simulations, and STEM approaches boost student engagement and conceptual understanding. PBL emerged as the most dominant model due to its adaptability across science topics and strong capacity to cultivate problem-solving abilities. However, HOTS implementation remains moderate owing to teacher competency gaps, student readiness, and sub-optimal technology integration. Future research should develop more innovative, technology-integrated learning strategies to optimize HOTS development in science education.